Aesthetic Performance Products as a Basis For Non Novelty of Industrial Design Based on The Public Domain Principle - Desy Rizki Ramadhani; Puteri Melati; Camellia Anand (Fakultas Hukum Universitas Airlangga, 2019)
Comparative products are very important and must be considered about it because, Industrial Design assesses the performance of products that can be proven from evidence that can be seen or assessed by clear eye such as photographic evidence, catalogs or other evidence that can be proved bye Industrial Design which has existed before. Industrial design is based on its external appearance which does not have an aesthetic impression and contradicts Article 1 point 1 of the Industrial Design Law and article 25 Paragraph 1 of the TRIPs agreement, which is form creation, solely for function or technical configuration. Aesthetically cannot be registered. In the absence of aesthetic elements, the product performance can be used as the basis for the absence of new industrial designs based on the principle of